Tingkatkan Fokus dengan Latihan Buttoning Skills pada Anak Mild Intellectual Disability - Khairunnisa, Nadira; Hartini, Nurul (Jurnal Psikologi Teori dan Terapan, 2022)
Children with intellectual disabilities have deficits in general mental abilities due to insignificant cognitive development. The deficits result in weak attention functions that difficulty maintaining focus and are easily distracted. Therefore, they failed to meet standards in responsibility including daily life aspects. Implementing behavior modification enhances mastery of daily life skills and also training focuses in order that children become more independent. This study aims to examine whether buttoning skills practice could increase focus on intellectual disability children. The experimental approach was carried out with a single case AB with backward chaining technique assisted by prompting and giving positive reinforcement. The participant was a 9-yearold girl with the initials ZR who was diagnosed with mild intellectual disability. Assessment based on accomplishment following the stages systematically. The results show there is an improvement trend in mastering buttoning skills. This is due to appropriate positive reinforcement being selected that motivated participants to focus on completing tasks. Repetition makes participants become more acclimated to wear button-up clothes. This skill practice could be an option to encourage focus on intellectual disability children. Anak dengan intellectual disability mengalami defisit intelektual sebab perkembangan kognisi yang tidak optimal. Kondisi ini menyebabkan lemahnya fungsi atensi yang merupakan faktor signifikan dari perkembangan kognitif. Akibatnya anak mengalami hambatan pada kemampuan dalam keterampilan adaptif, sosial serta konseptual. Akan tetapi anak mild intellectual disability masih dapat dibina walau perlu pendampingan. Mereka dapat diajarkan keterampilan sehari-hari untuk meningkatkan kemandirian. Keterampilan harian self-help dressing menjadi salah satu kebutuhan, termasuk berlatih memasang-melepas kancing (buttoning skills). Buttoning skills membutuhkan tahapan yang tersistematis sehingga membantu anak berkonsentrasi. Penelitian ini adalah single case AB design pada anak mild intellectual disability berusia 9 tahun. Intervensi yang digunakan adalah backward chaining dibantu teknik prompting dan pemberian positive reinforcement. Hasil buttoning skills dengan intervensi yang ditetapkan mendapatkan gambaran adanya peningkatan keterampilan serta membangun fokus dan dorongan pada anak.